2015
DOI: 10.1021/tx500479m
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxicity of Silver Nanoparticles to Red Blood Cells: Size Dependent Adsorption, Uptake, and Hemolytic Activity

Abstract: Silver nanoparticles (AgNPs) are increasingly being used as antimicrobial agents and drug carriers in biomedical fields. However, toxicological information on their effects on red blood cells (RBCs) and the mechanisms involved remain sparse. In this article, we examined the size dependent nanotoxicity of AgNPs using three different characteristic sizes of 15 nm (AgNPs15), 50 nm (AgNPs50), and 100 nm (AgNPs100) against fish RBCs. Optical microscopy and transmission electron microscopy observations showed that A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
158
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(179 citation statements)
references
References 43 publications
11
158
1
2
Order By: Relevance
“…We incubated the erythrocytes with vehicle or PVPor CT-AgNPs for 4 h; a time point similar to previous in vitro studies [18,31]. The various concentrations of PVP-and CT-AgNPs (2.5, 10 and 40 µg/ml) used in our study are also similar to previous studies evaluating nanotoxicity and blood compatibility of erythrocytes incubated with AgNPs [17,23]. Our concentrations are comparable with previous studies using AgNPs on human, mouse and fish erythrocytes and the highest dose of 40 µg/ml, is much lower than the optimal dose of AgNPs (200 µg/ml) that has been reported to induce hemolysis in human erythrocytes [17,18,23,[32][33][34].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We incubated the erythrocytes with vehicle or PVPor CT-AgNPs for 4 h; a time point similar to previous in vitro studies [18,31]. The various concentrations of PVP-and CT-AgNPs (2.5, 10 and 40 µg/ml) used in our study are also similar to previous studies evaluating nanotoxicity and blood compatibility of erythrocytes incubated with AgNPs [17,23]. Our concentrations are comparable with previous studies using AgNPs on human, mouse and fish erythrocytes and the highest dose of 40 µg/ml, is much lower than the optimal dose of AgNPs (200 µg/ml) that has been reported to induce hemolysis in human erythrocytes [17,18,23,[32][33][34].…”
Section: Discussionmentioning
confidence: 60%
“…In addition, studies using human erythrocytes have investigated the effects of AgNPs on hemolysis, morphology and their uptake [17,18]. Nevertheless, the mechanism underlying the pathophysiological effects of AgNPs on erythrocytes physiology is not fully understood.…”
Section: The In Vitro Effect Of Polyvinylpyrrolidone and Citrate Coatmentioning
confidence: 99%
“…53 Cytotoxicity of AgNPs on red blood cells (RBCs) is of particular interest, as the introduction of AgNPs into the body suggests a high probability of these into the blood. Chen et al 54 found cytotoxicity effects of 15, 50, and 100 nm AgNPs on RBC to be higher when they are a smaller size, while biological-based nanoparticles with larger sizes exhibit higher cytotoxic effects. This points to a possible difference in toxicity mechanism from one type of nanoparticle to the next.…”
Section: Toxicitymentioning
confidence: 99%
“…42 (Asp) 8 -PEG-PCL nanoparticles designed in this study had the hydrophilic surface of PEG and the hydrophilic The effect of nanoparticles on erythrocyte aggregation indicates hemocompatibility of the nanoparticles. 43 Copolymer containing PEG-PCL has been reported to be hemocompatible and biocompatible. 44,45 In this study, we found that (Asp) 8 -PEG-PCL nanoparticles were hemocompatible, and biocompatible to osteoblasts and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%